Differences in Morbidity and Mortality Rates in Black, White, and Hispanic Very Preterm Infants Among New York City Hospitals. Issue 6 (June 2018) - Howell, Elizabeth A.; Janevic, Teresa; Hebert, Paul L.; Egorova, Natalia N.; Balbierz, Amy; Zeitlin, Jennifer
Abstract : (Abstracted from JAMA Pediatr 2018;172:269–277) Currently, 98% of neonatal intensive care units (NICUs) have a risk-adjusted rate of mortality equal to the best 10% of units in 2005, a statistic showcasing the significant improvements in neonatal care over the past decade. Despite improvements, research shows significant racial disparities in neonatal mortality and morbidity, with non-Hispanic black neonates and Hispanic neonates experiencing a disproportionate amount of these adverse events.